Comparison of 30-day postoperative outcomes of open and minimally invasive pyeloplasty utilizing the prospective National Surgical Quality Improvement Program-Pediatric database. Issue 4 (August 2019) - Woo, K.; Bukavina, L.; Mishra, K.; Mahran, A.; Prunty, M.; Ponsky, L.; DiCarlo, H.; Ross, J.; Woo, L.
Summary: Introduction: Open pyeloplasty (OP) has traditionally been the standard for the operative management of ureteropelvic junction obstruction in children. With advances in minimally invasive pyeloplasty (MIP) techniques, it is quickly becoming a popular alternative in both adult and pediatric population. Objective: To evaluate the differences in outcomes between MIP and OP for the surgical correction of ureteropelvic junction obstruction in children. Study design: Data were obtained from the pediatric National Surgical Quality Improvement Program 2012–2017. We identified 1280 patients who underwent MIP and 1190 patients who underwent OP between 2012 and 2017. Propensity score matching was utilized to adjust for baseline differences. Univariate and multivariable regression were performed to assess odds of complications and procedure-related readmission. Results: Patients who underwent OP had a significantly decreased operative time (192.42 vs 142.00 min, p < 0.001) compared to MIP. There was no significant difference in the rates of overall peri-operative complications (3.7% [MIP] vs 2.4% [OP] p = 0.397). On multivariable analysis, patients undergoing OP had a lower risk of procedure-related readmission (odds ratio [OR] 0.404, 95% confidence interval [CI] 0.157–0.951, p = 0.046) than MIP. In a multivariable linear regression model, the risk of having any postoperative complication, regardless of surgical approach, decreased with increasing patient age (OR 0.945, 95% CI 0.893–0.996, p = 0.037). Discussion: Although recent small, retrospective institutional studies have found decreased hospitalization time of MIP as compared to OP, in our large prospective database, we found no such association. While some studies suggest a higher rate of wound complications in the OP group, this was not reproduced in our study as well. MIP was, in fact, associated with higher rate of readmissions as compared to the OP group, which may act as a surrogate of long-term complications in these patients. Conclusion: MIP offers an alternative to OP in the pediatric population with similar rates of peri-operative complications. However, our study shows decreased odds of procedure-related readmission in OP, which may serve as a surrogate for less postoperative complications in these patients.